Foreign direct-investment in ireland - empirical-evidence and theoretical implications - Oloughlin, b; ofarrell, pn; O'Farrell, PN (Economic & Social Studies, 1980)
This paper summarises the existing literature on foreign direct investment and the multinational enterprise with emphasis on those aspects which are particularly relevant to Ireland. Empirical analysis of data on new grant-aided manufacturing industry for the year 1976/77 shows that (i) the branch plants of overseas firms in Ireland tend to belong to relatively small parent companies and (ii) analysis of the capital intensity, technological sophistication and industrial linkages of domestic and overseas New Industry shows that the New Industry manufacturing sector is not characterised by a dual economy. It is concluded that the existing theory of foreign direct investment is deficient in that it tends to view the process from the perspective of the country undertaking the investment.
Keywords: Economics; Sociology